Plasticity in activity patterns of ungulates under the influence of shade coffee agricultural intensification in Ethiopia - Behailu Etana; Peter J. Fashing; Anagaw Atickem; Afework Bekele; Nils Chr. Stenseth (Global Ecology and Conservation)
A better understanding of mammalian activity patterns is essential for assessing responses to anthropogenic disturbances. Several ungulates play a crucial role in maintaining forest functions and are vulnerable to disturbances caused by humans. It is imperative to understand how this functional group reacts to the intensification of coffee forests. To address this issue, we investigated diel activity patterns and behavioral responses of ungulates in relation to the increasing intensity of coffee forest management systems (semi-forests, semi-plantations, and plantations) and nearby natural forests in the Belete-Gera National Forest Priority Area, southwest Ethiopia. We surveyed mammals using motion-detecting infrared camera traps at 90 stations (mean = 22.5 per forest; SD ± 5.5) for a total of 4142 cumulative camera days. In order to develop activity overlap plots, we fitted kernel density functions of activity times for six species of ungulates separately in managed coffee forests and compared to those in natural forests. Further, we compared behavioral response of ungulates using Non-metric multidimensional scaling. Our findings showed that with increasing intensity of coffee forest management, ungulate diel activity patterns shift primarily to crepuscular and nocturnal for bushbucks, giant forest hogs, and bushpigs, but not for bush duikers, warthogs and buffaloes. It is possible that this response is a result of forced inactivity during daylight hours that occurs in intensified coffee habitats where humans often disturb the environment. In addition, the behavioral responses showed that there was a distinct clustering of feeding, resting, and moving behavior patterns in the plantation coffee habitat. Thus, as the management intensity of shade coffee increases, the habitat quality for some ungulates decreases. It is essential to develop species-specific requirements in conservation measures to mitigate conflict with humans and propose effective management strategies. Additionally, humans should limit their movement in coffee forest habitats at night, in the early morning, and in the late afternoon to ensure coexistence with resident ungulates